Clinical profile and outcome of patients with placenta previa: a study at a tertiary care referral institute in Northern India - Jaiswal, Ekta; Aggarwal, Neelam; Suri, Vanita; Bagga, Rashmi; Kalra, Jasvinder; Gupta, Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study was to determine clinical profile, evaluate our antenatal and intraoperative management and see the maternal and perinatal outcome in patients with placenta previa. Methods: A prospective study was carried out in 130 women with placenta previa in the Department of Gynecology, PGIMER, Chandigarh, India between Jan 2015–April 2016. The profile of these patients was recorded in a predesigned proforma and maternal and perinatal outcome analyzed in detail. Results: One third (46/130) of the patients with placenta previa had a history of previous caesarian section, 27% had previous uterine curettage and 82% were multiparous.18% were asymptomatic placenta previa whereas 82% had one or more bleeding episodes. Expectant management was given to 67% patients after first bleeding episode. Majority (92/130) of patients required emergency cesarean section. Due to invasive placentation, 25 patients required cesarean hysterectomy. Ninety percent patients required delivery at ≤37 weeks and neonatal outcome improved with increasing gestation as expected. Conclusions: Reduction in cesarean rate is the major key factor for decreasing the incidence of placenta previa as, as well as placenta accreta and other associated complications as there were no patients diagnosed to have placenta accreta when placenta previa was present without any previous cesarean scar. In cases of invasive placenta, performing a classical CS, not trying to remove the placenta and proceeding directly to hysterectomy resulted in reduced blood loss. Neonatal outcome as well as maternal outcome is best when cesarean is done between 36-37 weeks.